(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this study, novel organic ammonium salts, 4-[(2Z)-3-carboxyprop-2-enoyl]- aminobenzoate tetraethyl ammonium, C1, 2-[(4-carboxyphenyl)carbamoyl]-benzoate tetraethyl ammonium, C2, 4-[(3-carboxypropanoyl)amino]-benzoate tetraethyl ammonium, C3, 2-[(4-carboxyphenyl)carbamoyl]-benzoate tetraethyl ammonium, C4, and the structures have been verified using spectroscopic methods. The recently developed organic ammonium salts were used as corrosion inhibitors to protect mild steel from corrosion. The experimental procedure included putting organic salts in a 3.5% saline solution for 24 hours at room temperature. The weight-loss technique was used to assess the effects of this treatment. The findings referring to the inhibition effectiveness of organic inhibitors (C1–C4) showed an increase as the concentrations of organic ammonium salts rose. This rise in inhibition efficiency was shown to be followed by a reduction in the corrosion rate. The increased level of inhibitory efficiency resulted in a rise in the coated surface degree factor. The thermodynamic parameter, namely the free energy, was anticipated to determine the physisorption impact of several organic ammonium salts (C1–C4).